2010
DOI: 10.1016/j.physleta.2010.03.037
|View full text |Cite
|
Sign up to set email alerts
|

Universal features of polymer shapes in crowded environments

Abstract: We study the universal characteristics of the shape of a polymer chain in an environment with correlated structural obstacles, applying the field-theoretical renormalization group approach. Our results qualitatively indicate an increase of the asymmetry of the polymer shape in crowded environment comparing with the pure solution case.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…In particular, it was shown that the correlated obstacles in environment lead to a new universality class with values of the polymer scaling exponents that depend on the strength of correlation expressed by parameters a. The question about how the characteristics of shape of a flexible chain are effected by the presence of such a porous medium was briefly discussed by us in reference [45]. The details of these calculations will be presented here.…”
Section: Polymer In Porous Environment: Model With Long-range Correlamentioning
confidence: 99%
“…In particular, it was shown that the correlated obstacles in environment lead to a new universality class with values of the polymer scaling exponents that depend on the strength of correlation expressed by parameters a. The question about how the characteristics of shape of a flexible chain are effected by the presence of such a porous medium was briefly discussed by us in reference [45]. The details of these calculations will be presented here.…”
Section: Polymer In Porous Environment: Model With Long-range Correlamentioning
confidence: 99%
“…Presence of disorder in the form of extended structural defects causes the swelling of polymer coil (1) with larger value of scaling exponent ν, and thus leads to an elongation of polymer conformation. Further studies reveal an increase of the effective polymer size and shape anisotropy of polymers in long-range correlated disorder [51]. Moving from linear polymer chains to more complicated structures like star-branched polymers in environment with long-range correlated disorder, one finds the whole spectrum of universal exponents in a new universality class [52].…”
Section: Introductionmentioning
confidence: 99%
“…The origin of the coordinate system is the centre of mass. The inertia tensor is defined by the expression [4][5][6][7][8]:…”
Section: Introductionmentioning
confidence: 99%